Gray, Wendell. The Gray stage in Quidi Vidi. - Sawden, Kari (2013)
Stage built in 2009 by Wendell and Balfour Gray, replacing the one built by their father, Joseph "Skipper" Gray, that was destroyed in the winter of 2009.